Correction: A novel approach for detection and quantification of magnetic nanomarkers using a spin valve GMR-integrated microfluidic sensor. Issue 37 (29th March 2016) - Devkota, J.; Kokkinis, G.; Berris, T.; Jamalieh, M.; Cardoso, S.; Cardoso, F.; Srikanth, H.; Phan, M. H.; Giouroudi, I.
Abstract : Abstract : Correction for 'A novel approach for detection and quantification of magnetic nanomarkers using a spin valve GMR-integrated microfluidic sensor' by J. Devkota et al., RSC Adv., 2015, 5, 51169–51175.